Summary of the 2010 AHPBA/SSO/SSAT Consensus Conference on HCC - Gitonga Munene; Jean-Nicolas Vauthey; Elijah Dixon (International Journal of Hepatology)
Under the auspices of the American Hepato-Pancreato-Biliary Association, an expert consensus conference was convened in January 2010 on the multidisciplinary management of hepatocellular carcinoma. The goals of the conference were to address knowledge gaps in the optimal preparation of patients with HCC for operative therapy, best methods to control HCC while awaiting liver transplantation, and developing a multidisciplinary approach to these patients with implementation of novel systemic therapies.